ORIGINAL PAPERClinical application of CardioSEAL/STARFlex devices for transcatheter closure of atrial septal defect, patent foramen ovale and patent ductus arteriosus - Białkowski, Jacek; Szkutnik, Małgorzata; Kusa, Jacek; Baranowski, Jacek; Banaszak, Paweł; Żyła-Frycz, Maria; Kapik, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2006)
CardioSEAL/STARFlex devices (CS/SF) are double umbrella systems, which have several technical advantages such as: low profile, low nitinol content and relatively large covering surface. Our clinical experience with application of those devices is presented. Material and methods: From 1999 till 2005 transcatheter closure of undesirable shunts with CS/SF was performed in 45 patients (pts). They were divided into 3 groups: – Atrial Septal Defect (ASD): 32 pts aged 12.3 (4 to 27) years; – Persistent Foramen Ovale (PFO): 10 pts aged 31.7 (13 to 54) years; – Patent Ductus Arteriosus (PDA): 3 pts aged 16, 17 and 62 years. Indications for CS/SF implantations were: – in ASD: small, centrally located defect or multifenestrated aneurysm of the interatrial septum (IAS); – in PFO: history of cryptogenic transient ischemic attacks or stroke and right to left shunt through short PFO tunnel (<8 mm) on Valsalva maneuver; – in PDA: large, window type duct. Standard transvenous technique of CS/SF implantation was applied in all pts. Results: In all but 2 pts the procedures were completed successfully. The reason of 2 procedural failures during ASD closure was unsatisfactory umbrella position. Complete closure of undesirable communications was achieved in all but one pt with multiperforated aneurysm of IAS. In the latter pt the residual shunt was of no haemodynamic significance. Conclusions: Transcatheter closure of some ASD, PDA and PFO with Cardioseal/Staflex umbrella can be the treatment of choice in a selected group of patients.